PENGARUH INOKULASI JAMUR MIKORIZA ARBUSKULA TERHADAP GLOMALIN, PERTUMBUHAN DAN HASIL PADI - Jauhari Syamsiyah; Bambang Hendro Sunarminto; Eko Hanudin; Jaka Widada (Faculty of Agriculture, Universitas Sebelas Maret, 2014)
TITLE : EFFECT OF ARBUSCULAR MYCORRIZHAL FUNGI INOCULATION ON GLOMALIN, GROWTH AND RICE YIELD. The aim of this study was to measure the glomalin production, growth and yield of rice in upland rice fields. The research used Completely Randomized Design with four treatments: two sterilization levels (no sterilisatio and with sterilization) and two levels of mycorrhizae inoculation ( no mycorrhizae and with mycorrhizae). Mycorrhizae (5 g/pot) was inoculated before planting rice seeds. The results showed that Glomalin Total (GT) and Glomalin easily extracted (GEE) were higher in mycorrhizae inoculation, increased by 16% and 20% in non-sterile soil and 25% and 11% in sterile soil compared to non-mycorrhizae inoculation. The content of the GT ranged from 4.95 to 9.74 mg/g soil and GEE 0.99 to 2.78 mg/g soil. Plant height, tillers number and the grain yield was increased by mycorrhizae inoculation significantly. Soil sterilization could reduce the effectiveness of mycorrhizae inoculated.